If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4w + -1) = 8 Reorder the terms: -3(-1 + 4w) = 8 (-1 * -3 + 4w * -3) = 8 (3 + -12w) = 8 Solving 3 + -12w = 8 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -12w = 8 + -3 Combine like terms: 3 + -3 = 0 0 + -12w = 8 + -3 -12w = 8 + -3 Combine like terms: 8 + -3 = 5 -12w = 5 Divide each side by '-12'. w = -0.4166666667 Simplifying w = -0.4166666667
| x^2+2xi+11-16i=0 | | 3(1+4b)-b=-85 | | 5y/9/2y=23 | | 4/1^(1/2)-x^(1/2) | | 5x(6-3x)=12 | | -3x-7x/5=5x-(x3) | | 4x+4(2x+10)=100 | | -7/(7/18) | | -4g=-84 | | (2x/5)-(x/2)=40 | | (3/5)x=-6 | | 14-8w=-130 | | (2x/5)-(x/20)=40 | | 3x+3(4x-20)=75 | | 8h=56 | | 7x(4x+3)=5 | | 9+6x=6x+2+4 | | 4t-t-7=2t-4 | | 5(10-3x)=30 | | 16=-5y | | -37=-7x+5(x-5) | | 5x+x-3=5x+6 | | 16y=-5y | | 1/3(8x-1)^2+19=94 | | +111-1-1-1+6+1=23*5 | | +111-1-1-1+6+1=23x | | 13x+6-7=1+8x | | -1-1-1-1-1-1-1+6+1=23x | | 75=v/3 | | 5x+7(x+19)=217 | | 2n+4n+3n=-18+5n | | -12=6w |